Correlation of SNPs in Myeloid differentiation-2 (MD-2) gene with the susceptibility to clinical mastitis in Chinese Holstein dairy cows - XU, JINGCHENG; GUO, SHANSHAN; TANG, XINSHENG; CAI, YAFEI (The Indian Journal of Animal Sciences, 2021)
Myeloid differentiation-2 (MD-2), as an essential component of the CD14-TLR4/MD-2 receptor complex, is critical in identifying bacterial Lipopolysaccharide (LPS) and activating innate immune responses. To evaluate the relationship between MD-2 polymorphisms (including 5′ end and exon regions) and clinical mastitis, population genetic analysis was performed via PCR single strand conformation polymorphism (PCR-SSCP) and direct sequencing in Chinese Holstein dairy cows. Eleven pairs of primer PCR products for SSCP analysis: six pairs of primers (P1-P6) for the 5′-end, four (P7–P10) for the exon regions, and one (P11) for 3′-untranslational region. There were six SSCP bands (named: EE, EF, FF, EQ, EM and EN genotype) in the PCR amplification products of primer P1, two bands in P4 (CD and DD) and three bands in P5 (AA, AB, and BB). Total of five (g.-2173 C/G, g.-2148 C/T, g.-2089 G/T, g.-555 G/A and g.-121 C/A) single nucleotides polymorphism sites (SNPs) were identified in 5′-end of the MD-2 gene. Data showed that SNPs g.-555 (G/A) had significant differences (P